2019
DOI: 10.1111/jir.12618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor skill interventions on fundamental movement skills in children and adolescents with intellectual disabilities: a systematic review

Abstract: Background Children and adolescents with intellectual disabilities (ID) are characterised by deficits in fundamental movement skills (FMS). In youth with typical development, motor skill interventions have been recognised as an efficient means to improve FMS. However, the effects of these interventions among youth with ID have not yet been systematically reviewed. Purpose The purpose of the present systematic review was to summarise the findings from studies pertaining to the effects of motor skill interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…The implementation of a professional development programme, designed to support ECE teachers to promote young children’s healthy eating and PA, has also significantly improved FMS [ 64 ]. Such improvements in FMS have been reported in preschoolers who live with, and those who live without, developmental delays [ 41 , 42 , 65 ]; these improvements were not seen in a low socioeconomic ECE center with low levels of adherence to the intervention [ 66 ]. However, directly comparing the results of such interventions can be difficult because of differences in intervention type, methodology and assessment tools [ 62 ].…”
Section: Discussionmentioning
confidence: 67%
“…The implementation of a professional development programme, designed to support ECE teachers to promote young children’s healthy eating and PA, has also significantly improved FMS [ 64 ]. Such improvements in FMS have been reported in preschoolers who live with, and those who live without, developmental delays [ 41 , 42 , 65 ]; these improvements were not seen in a low socioeconomic ECE center with low levels of adherence to the intervention [ 66 ]. However, directly comparing the results of such interventions can be difficult because of differences in intervention type, methodology and assessment tools [ 62 ].…”
Section: Discussionmentioning
confidence: 67%
“…Compared with youths with typical development between the ages of 7 and 12 years, youths with IDs tend to have significantly lower motor proficiency skill levels in terms of fundamental movement [ 6 ] and locomotor and object control [ 5 , 6 , 8 ]. A systematic review summarized the findings of 14 studies concerning youths with IDs aged 5 to 22 and revealed that PA interventions are efficient in improving fundamental movement skills (i.e., locomotion, object control, and balance skills) [ 32 ]. Most of the studies focused on the balance skills of youths with mild IDs and offered strong support for the effect of PA interventions on balance skills.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports the beneficial effect of PA interventions on motor proficiency in younger youths with IDs (aged 6–11 years); however, it is currently unclear whether the effects of PA interventions are effective in improving motor proficiency in older youths with IDs (aged 12–17 years) [ 32 ]. To date, only three studies have examined the effects of PA interventions on changes in motor proficiency of older youths with IDs.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, children with disabilities also engage in lower rates of physical activity (19)(20)(21), participate in fewer leisure and recreational activities (22)(23)(24), exhibit poor healthrelated physical fitness (25)(26)(27), and have higher proportions of children with overweight and obese weight status (28)(29)(30). Despite significant deficits and delays, multiple intervention studies have shown that children with disabilities can improve FMS competence if these skills are directly taught and practiced (31)(32)(33). Thus, identifying FMS delays in preschoolers with disabilities is particularly important so that early intervention to remediate these delays in FMS may begin.…”
Section: Introductionmentioning
confidence: 99%